The role of gut microbiota in the formation of IBD, a typical chronic intestinal inflammatory disease - Chen, Jinglin (Frontiers in Microbiology, 2025)
The existing etiological studies of inflammatory bowel disease (IBD) mainly focus on genetics, environment, immunity and gut microbiota (GM). Interestingly, this review found that the first three causes are not separate, but closely related to GM. First, the genetic characteristics of GM are closely related to the pathogenesis of IBD, and multiple human genomic loci (such as LCT and ABO) have been identified to affect GM changes and increase the risk of IBD. Secondly, the composition of GM is directly related to the environment at birth. With the growth of human beings, environmental factors such as diet, antibiotics, and even psychosocial stress can lead to significant changes in the composition and function of the GM, thus affecting the intestinal inflammatory state of the host. In addition, GM disruption stimulates the body to accumulate a large number of inflammatory cells and activates the immune system to repair tissue while resisting infection, resulting in colitis. Therefore, this review takes genetic factors, environmental factors, and immune regulation as entry points to explore the important role of GM in the formation of colitis and the possible benefits of regulating GM composition, providing new strategies for the prevention and treatment.